Political Dynamics that Rooted the Boko Haram Insurgence and Impediments against its fight in Nigeria - Olalekan, Aliyu Lukman (Kashere Journal of Politics and International Relations, 2025)
Boko Haram insurgence has become a major security issue confronting Nigerian state since 2009. Seismic damages have been done over the years in respect of lives and properties. Indeed, socio- political stability and economic life of the country has been negatively touched owing to persistence insurgence. This study investigates political dynamics in Nigeria that are rooted the Boko Haram Insurgency as well as examines the contextual stances that obstructed successful fight against the Insurgency in Nigeria. Qualitative method of inquiry was adopted, as secondary data were analysed. This study found that political failure, religious fragmentation and dashed hope (expectations) in Northern Nigeria are the root courses of Boko Haram insurgency. These tripod variables metastasized in form of: fraudulent elections, corruption, inequality, instrument of violence and impunity and politics of Shari’a Law adoption and its implementation. Also this study identified: Bad governance, perceived political affiliation, mineral exploration and exploitation, missing political framework, lack of sophisticated equipment/corruption and uncoordinated/division among the military hierarchy as major impediments obstructing the successful fight against the insurgency in Nigeria. Prioritization of good governance, de-politicization of sensitive religious issues, government pro-activeness and responsiveness to religiously garmented matters and fulfillment of promises made by the Northern political leaders are some recommendations offered by this study. This became necessary owing to the fragility and the need for peace, stability and development of not only the Northern region but Nigeria as a whole.